Merajut Kualitas Islami: Strategi Transformasi Sistem Penjaminan Mutu PAI Menuju Madrasah Ibtidaiyah Unggul - Kutbaniyah, A'imatul; Faslah, Romi (Prodi Pendidikan Keagamaan Islam, 2025)
Madrasah Ibtidaiyah (MI) has a dual mandateto educate the mind and purify the spirit, but faces a dilemmaof quality where Islamic Religious Education (PAI) often falls intoa cognitive-verbalistic approach and the Internal Quality Assurance System (SPMI)is trapped in administrative routines. This study aims to formulate a specific Strategy for the Transformation of SPMI PAI to present the IslamicQuality Culture (IQC) Model, which shifts the function of SPMI from document complianceto a tool for shaping Islamic character and excellence. The method usedis Library Research withconceptual-critical analysis to construct a transformative model. As a result, this studyoffers an IQC Model that integrates the PDCA (Plan-Do-Check-Act) quality cycle with Islamic values such as itqan (perfection) and Amanah (moral-spiritual responsibility). This transformation requires the establishment of standards that measure the affective and psychomotor dimensions of PAI, as well as shifting SPMI fromadministrative routines to a mechanism for real improvement in the teaching and learning process, with the ultimate impact of creating an Excellent Madrasah Ibtidaiyah thatproduces graduates with strong character.